A comparison of the separation efficiency of dissolved and dispersed oil using microfiltration and ultrafiltration membrane - Khor, Ee Huey; Samyudia, Yudi (ICMS Pty Ltd, 2010)
In this paper, membrane filtration was incorporated as part of oil-in-water analysis to separate dispersed and dissolved oil so that the accuracy of measuring the dispersed oil concentration can be enhanced. In the previous study, Microfiltration (MF) and some Ultrafiltration (UF) were discovered to be able to separate dissolved oil from the produced water. The primary aim of this paper is therefore to improve the efficiency of the separation by exploring different types and sizes of membrane and by adjusting differential pressure while the effectiveness of these membranes in the separation of dissolved oil are measured by its concentration using Gas Chromatography with Mass Spectrophotometer detector (GC-MS). To achieve an efficient separation, two objectives need to be addressed which are: maximizing the amount of dissolved oil in permeate and maximizing the amount of dispersed oil in retentate. The efficiency of separation and the interactions among the factors for these objectives are then statistically analyzed. The separation of dissolved oil in permeate is enhanced by using microfiltration membrane.